2017
DOI: 10.3851/imp3087
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with HBV Virological Breakthrough

Abstract: BREAKTHROUGHBackground: Little is known about non-adherence to Hepatitis B virus (HBV) therapy.This study aimed to investigate the relationship between self-reported missed days of anti-viral therapy and HBV virological breakthrough and factors associated with virological breakthrough.Methods: A cross-sectional survey of 211 HBV patients receiving oral anti-viral therapies was undertaken at three tertiary hospitals in Sydney, Australia. Associations between 0 to > 6 missed days in the last 30 days and virologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…From an initial screen of 878 titles, 30 studies providing data for 23,823 patients met our eligibility criteria and were taken through for review (Fig. ) . The majority (23 studies, 17,057 patients) were from high‐income settings, mainly the United States (seven studies), Australia (four studies), and France (three studies).…”
Section: Resultsmentioning
confidence: 99%
“…From an initial screen of 878 titles, 30 studies providing data for 23,823 patients met our eligibility criteria and were taken through for review (Fig. ) . The majority (23 studies, 17,057 patients) were from high‐income settings, mainly the United States (seven studies), Australia (four studies), and France (three studies).…”
Section: Resultsmentioning
confidence: 99%
“…(17,18,220,221) Virological breakthroughs, defined as a >1 log 10 (10-fold) increase in serum HBV DNA from nadir after initial virological response, may be related to medication nonadherence, so adherence should be ascertained before testing for genotypic resistance. (222) Virological breakthrough is usually followed by biochemical breakthrough, defined as ALT elevation during treatment in a patient who had achieved an initial biochemical response. Emergence of antiviral resistance mutations can lead to negation of the initial response and, in some cases, hepatitis flares and hepatic decompensation.…”
Section: F Treatment Of Patients With Virological Failure On Na Thementioning
confidence: 99%
“…To the best of our knowledge, this is the first study to comprehensively assess the associations between risk factors and non-adherence to HBV anti-viral therapy using an evidence based definition [18]. Previous studies have investigated limited demographic, treatment and diseaserelated factors.…”
Section: Discussionmentioning
confidence: 99%
“…Using an established evidence base definition for non-adherence [18] this study aimed to 1) measure the frequency of self-reported non-adherence to HBV anti-viral medications in the last 30 days and 2) identify predictors of self-reported non-adherence.…”
mentioning
confidence: 99%